Authenticity dan Immersion di Theme Park Rasamadu Heritage, Solo - Aji, Alfi Turni; Salsabila, Adya Danastri; Angelin, Chintya (JURNAL NASIONAL PARIWISATA, 2025)
Rasamadu Heritage is a European-style amusement park located in Solo. Due to the branding as “Wisata Solo Rasa Eropa”, this destination provides attractions in the form of photo spots such as European-style buildings, transportation museum, and the newest attraction that is Cubic Infinity Room. Cubic Infinity Room is an indoor photo spot decorated with colorful lights that emphasize the tourists’ immersion experience. Cubic Infinity Room rapidly became the main attraction for tourists. This research was conducted using descriptive qualitative methods to analyze the theme coherence and what attempts can be done to strengthen the identity of Rasamadu Heritage. The study’s findings show that there are some issues in this destination such as incoherence of the promotion and the actual attractions in this theme park. This issue affects the authenticity and the immersion concept in Rasamadu Heritage which leads to non optimal tourists’ experience. Through the results that are collected from interviews, field observation, and social media, not a few tourists have expressed dissatisfaction and criticism of the problems in this destination. Based on research findings, the development of Rasamadu Heritage may pay attention to the aspects of authenticity and immersion to create a satisfying experience for tourists.